Small and orthodox fiscal multipliers at the zero lower bound - R. Anton Braun; Lena Mareen Körber; Yuichiro Waki (Federal Reserve Bank of Atlanta, 2013)
Does fiscal policy have large and qualitatively different effects on the economy when the nominal interest rate is zero? An emerging consensus in the New Keynesian literature is that the answer is yes. New evidence provided here suggests that the answer is often no. For a broad range of empirically relevant parameterizations of the Rotemberg model of costly price adjustment, the government purchase multiplier is about one or less, and the response of hours to a tax cut is either negative or close to zero.
Keywords: E5; E6; 330; monetary policy; zero interest rate; fiscal multipliers